2016
DOI: 10.4028/www.scientific.net/kem.706.63
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Layer Thickness on Mechanical Properties of the 3D Printed ABS Polymer by Fused Deposition Modeling

Abstract: 3D Printed ABS polymer samples were investigated for understanding the effect of layer thickness on the various mechanical properties of the component. Standard samples with varying layer thickness were prepared by 3D printing machine which works on the principle of Fused Deposition modeling (FDM) method and compared with sample prepared by standard injection molding method. Results show that tensile strength (36 MPa), impact strength (103.6 J/m) and hardness (R107) were highest for the samples made by injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 11 publications
5
24
1
Order By: Relevance
“…Although the differences in the mechanical properties between FDM ABS and conventionally manufactured ABS have been discussed in the literature [ 10 , 11 , 12 , 13 , 14 , 15 ], the most common conclusion was that FDM ABS has 11% to 37% reduced modulus and 22% to 57% reduced strength [ 16 , 17 ]. Some studies evaluated the different printing parameter effects on FDM ABS mechanical properties (strength and modulus) [ 18 , 19 , 20 , 21 , 22 , 23 ]. Some studies attempted to improve the mechanical properties of FDM polymers by optimising the 3D printing parameters [ 13 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the differences in the mechanical properties between FDM ABS and conventionally manufactured ABS have been discussed in the literature [ 10 , 11 , 12 , 13 , 14 , 15 ], the most common conclusion was that FDM ABS has 11% to 37% reduced modulus and 22% to 57% reduced strength [ 16 , 17 ]. Some studies evaluated the different printing parameter effects on FDM ABS mechanical properties (strength and modulus) [ 18 , 19 , 20 , 21 , 22 , 23 ]. Some studies attempted to improve the mechanical properties of FDM polymers by optimising the 3D printing parameters [ 13 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that maximum impact strength was achieved with increasing layer thickness to 0.2540 mm, and higher tensile strength reported against decreasing layer thickness to 0.1270 mm. Shubham et al [10] investigated the effect of layer thickness on the impact strength of PLA/PHA composite. Increasing layer thickness improves the impact strength due to uniformity of molecular bond and homogeneity within the layers.…”
Section: Introductionmentioning
confidence: 99%
“…Sood et al [28] concluded that an increase of around 15% in mechanical performance could be achieved when building with thinner road thickness. Wu et al [29] and Shubahm et al [30] observed that the presence of microvoids was smaller for thinner road thickness. Ning et al [31] also observed a similar effect, where the lower thickness led to considerable inter-bonding strength.…”
Section: Resultsmentioning
confidence: 99%